Induction Chemotherapy for Locoregionally Advanced Sinonasal Squamous Cell Carcinoma - Abiri, Arash; Liu, Derek H.; Nguyen, Theodore V.; Pang, Jonathan C.; Torabi, Sina J.; Kuan, Edward C. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background There is emerging evidence to suggest the role of induction chemotherapy (IC) in definitive management of locoregionally advanced sinonasal squamous cell carcinoma (SNSCC). We evaluated the influence of IC on survival and predictors of its use in SNSCC patients.Methods The 2004 to 2017 National Cancer Database was queried for patients with locoregionally advanced SNSCC (T4/M0). Treatments were stratified into seven groups: definitive chemoradiation (CRT), IC with definitive CRT (IC + CRT), IC + CRT with salvage surgery (IC + CRT + Sx), definitive surgery (Sx), IC with definitive surgery (IC + Sx), definitive surgery with adjuvant radiation or CRT (Sx + ATx), or IC + Sx + ATx. Cox proportional-hazards regression assessed overall survival (OS) and logistic regression identified predictors of IC.Results Of 3,162 patients, 1,088 (34.4%) were female with a mean age of 63.4 ± 13.4 years. The 2- and 5-year OS rates were 58.6 and 42.0%, respectively. Compared with CRT, Sx + ATx (hazard ratio [HR]: 0.663; p < 0.001), IC + Sx (HR: 0.606; p = 0.005), or IC + Sx + ATx (HR: 0.468; p = 0.001) exhibited reduced mortality. Among patients who were treated with definitive surgery, those receiving IC had additional OS benefit (all ps < 0.05). Older age (odds ratio [OR]: 0.607; p < 0.001), female sex (OR: 0.759; p = 0.028), Black race (OR: 1.650; p < 0.001, T4b stage (OR: 1.674; p < 0.001), and higher N stage (OR: 1.395; p < 0.001) were predictors of IC.Conclusion IC prior to definitive surgery with or without adjuvant therapy exhibited the highest OS for locoregionally advanced SNSCC. Age, sex, race, and T/N staging were predictors of IC. Multimodal treatment regimens involving surgery as the primary modality may, therefore, provide the greatest therapeutic response.
Keywords: sinonasal carcinoma; neoadjuvant chemotherapy; induction chemotherapy; survival; outcomes research